BUDAYA KERJA AGILE DAN KINERJA PEMASARAN DIGITAL: PERAN MEDIASI KOMPETENSI DIGITAL DAN MODERASI KEPEMIMPINAN TRANSFORMASIONAL - Dea Restika; Sulaeman, Maman (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2025)
This research explores the influence of agile work culture on digital marketing performance at Shopee Indonesia, with employee digital competence as a mediator and transformational leadership as a moderator. Using a quantitative approach with explanatory design, data were collected from 237 Shopee Indonesia employees through structured questionnaires and analyzed using Structural Equation Modeling (SEM). The results reveal that agile work culture positively and significantly influences digital marketing performance (β = 0.487, p < 0.05). Employee digital competence proves to function as a partial mediator in this relationship with a significant indirect effect (β = 0.209, p < 0.001). Transformational leadership positively and significantly moderates the relationship between agile work culture and digital marketing performance (β = 0.198, p < 0.05). The mediated moderation analysis reveals that the indirect effect of agile work culture on digital marketing performance through digital competence increases with higher levels of transformational leadership (from 0.153 at low levels to 0.287 at high levels). These findings provide strategic implications for e-commerce companies in optimizing digital marketing performance through the integration of agile culture, development of digital competence, and implementation of transformational leadership style